Diet quality and nutritional status in people living with HIV on dolutegravir therapy - Saraiva, Maria da Conceição; Lauar Gonçalves, Juliana; Dias Lula, Mariana; Caivano, Simone; Furtado Dos Santos, Simone; Gomes, Patrícia Ferreira; Oliveira, Emmanuelle Dutra; Braga, Maria das Graças (AIDS care, 2025)
While antiretroviral therapy (ART) has improved life expectancy for people living with HIV (PLWHIV), it has also brought new health challenges, including poor diet quality and excess weight. This cross-sectional study evaluated the diet quality and nutritional status of PLWHIV on dolutegravir (DTG)-based therapy in a Brazilian specialized care service. Adults (≥18 years) who initiated DTG between February 2017 and March 2020 were included. Data on sociodemographic, clinical, anthropometric, and dietary aspects were collected through interviews and medical records. Among the 148 participants (92.6% men, mean age 39.2 years), 48.0% were overweight and 24.3% had abdominal obesity. Overweight and obesity were more common among older individuals and those with higher baseline BMI. Abdominal obesity was also associated with lower education, being single, and lower CD4+ T-cell counts. Most women had abdominal obesity, despite most men being of normal weight. Diet quality was poor or intermediate in nearly all participants, marked by low intake of fresh foods and high consumption of ultra-processed items. No correlation was found between diet quality and nutritional status. The findings highlight the need for nutritional monitoring and interventions that also incorporate psychosocial and structural determinants of health among PLWHIV on DTG.